(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2021)
This study examines the cultural values that underlie social changes in the fishing community of Makassar City, with the Paotere Harbor Fish Auction Place as its economic locus. The type of research is library research. The data were collected using a sociological approach and using the theory of strategy and social change as the analytical framework. This study found three important things: first, the economy of the fishing community experienced a drastic change towards stagnation after the Covid-19 pandemic, second, the value system and cultural values of the local community were also affected, where the values of harmony ended in conflict, third, the government’s strategy to facing social changes due to the non-integrative covid-19 pandemic, so that one community problem was able to be resolved and the negative impact of covid-19 was slightly eliminated, but on another issue, in the sector which still involves fishermen and marine livelihoods, fishing communities feel disadvantaged.